2017
DOI: 10.2147/ijn.s133295
|View full text |Cite
|
Sign up to set email alerts
|

The interactions of single-wall carbon nanohorns with polar epithelium

Abstract: Single-wall carbon nanohorns (SWCNHs), which have multitudes of horn interstices, an extensive surface area, and a spherical aggregate structure, offer many advantages over other carbon nanomaterials being used as a drug nanovector. The previous studies on the interaction between SWCNHs and cells have mostly emphasized on cellular uptake and intracellular trafficking, but seldom on epithelial cells. Polar epithelium as a typical biological barrier constitutes the prime obstacle for the transport of therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…For example, a recent work constructed a drug vector (oxidized singlewall carbon nanohorns) that can be retained for a long time in the intes tine of mice due to their surface adhesion and endocytosis into the intestinal epithelium. [71] Besides the intrinsic properties of NMs, the utilized model is also an unnegligible factor for the assessment of nanotoxicity on IECs. For example, CuO NMs showed totally different behavior on the morphology of both differentiated and undifferentiated monolayer models of Caco2 cells (Figure 5c).…”
Section: Nano-iec Interaction and Subsequent Biological Effectsmentioning
confidence: 99%
“…For example, a recent work constructed a drug vector (oxidized singlewall carbon nanohorns) that can be retained for a long time in the intes tine of mice due to their surface adhesion and endocytosis into the intestinal epithelium. [71] Besides the intrinsic properties of NMs, the utilized model is also an unnegligible factor for the assessment of nanotoxicity on IECs. For example, CuO NMs showed totally different behavior on the morphology of both differentiated and undifferentiated monolayer models of Caco2 cells (Figure 5c).…”
Section: Nano-iec Interaction and Subsequent Biological Effectsmentioning
confidence: 99%
“…Therefore, it is very essential to compare these two types of nanocarbons in terms of their nanosafety and principles. Currently there are few studies, such Miyawaki et al tested the acute toxicities of SNH choosing CNT as one of references 11 – 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several studies have reported their effectiveness [14,15]. It has also been found that oxidation treatment makes CNHs hydrophilic, reduces aggregation, and enhances biocompatibility [16]. Although there are several reports on the pharmacokinetics of the poorly biodegradable CNHs, details about only relatively large accumulation sites have been revealed due to the poor detection sensitivity of CNHs [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%